Additional parameters for elucidation of the dielectric behavior of stator winding in high voltage motors - Norasage Pattanadech; Natthawut Phloymuk; Pethai Nimsanong; Chissanupong Srinangyam; Siwakorn Jeenmuang; Chanin Bunlaksananusorn (My University, 2022)
This paper proposes additional parameters for describing the dielectric behaviors of the stator winding in high voltage motors used in coal power plants. The on-site MV induction motors with indirect air-cooling rated 6.6 kV, 260 to 3091 kW, were investigated. These motors were installed in different parts of the plants and operated under different conditions. Therefore, the stator winding conditions of such motors were different. The integral insulation conditions of stator winding were examined by analysis of the dielectric response. Whereas the local insulation conditions of the stator winding, the so-called weak spot condition, were examined by analysis of the off-line PD test results. To deeply understand the dielectric behavior of such stator windings, a proposed simplified equivalent circuit for modeling the insulation system of the stator winding was introduced and constructed, which aimed to distinguish the dielectric behavior into conductivity, polarization, and ionization mechanisms. The additionally parameters, i.e., the minor capacitance (Ci), the minor resistance (Ri), the dc resistance (Rdc), the minor capacitance at defect site (CPD), the conductivity loss factor (Tan δσ), and the polarization loss factor (Tan δpol) were estimated and proposed. It can be concluded that the proposed additional parameters are a valuable tool for assessing the insulation condition, which reduces the ambiguity in the interpretation of the insulation test results and is suitable for monitoring insulation conditions over the service life of the high voltage motors.
Keywords: Dielectric loss; Insulation system; Power Transformer Diagnostics and Insulation